2019
DOI: 10.1097/iop.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Vismodegib and Mohs Micrographic Surgery for Locally Advanced Periocular Basal Cell Carcinoma

Abstract: Introduction: Vismodegib has shown a significant response rate in locally advanced periocular basal cell carcinoma. Long-term monotherapy is very difficult to accomplish due to primary or secondary resistance and side effects that limit the length of treatment. The use of Vismodegib as neoadjuvant followed by Mohs micrographic surgery is an option. Purpose: To report the use of neoadjuvant Vismodegib as an option for operable locally advanced basal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 18 publications
4
30
2
Order By: Relevance
“…The pivotal study, a prospective nonrandomized clinical trial, revealed a 43% response rate among patients with locally advanced BCC and 30% response rate among patients with metastatic BCC, with a median duration of response of 7.6 months [ 8 ]. Prospective trials have assessed vismodegib as a neoadjuvant in a variety of body locations [ 17 , 18 , 19 ], and several case studies have highlighted the efficacy of vismodegib for preserving vision in patients with orbital BCC [ 20 , 21 , 22 , 23 , 24 , 25 ]. More recently, post hoc prospective analysis of the multisite multicountry Safety Events in Vismodegib study data showed either complete or partial response to vismodegib in 67% of patients [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pivotal study, a prospective nonrandomized clinical trial, revealed a 43% response rate among patients with locally advanced BCC and 30% response rate among patients with metastatic BCC, with a median duration of response of 7.6 months [ 8 ]. Prospective trials have assessed vismodegib as a neoadjuvant in a variety of body locations [ 17 , 18 , 19 ], and several case studies have highlighted the efficacy of vismodegib for preserving vision in patients with orbital BCC [ 20 , 21 , 22 , 23 , 24 , 25 ]. More recently, post hoc prospective analysis of the multisite multicountry Safety Events in Vismodegib study data showed either complete or partial response to vismodegib in 67% of patients [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant therapy in Mohs surgery of eyelid tumours is a relatively new approach with the majority of reports considering the use of vismodegib for extensive periocular basal cell carcinoma 10 . Our case presents the first published report where neoadjuvant pembrolizumab was used to significantly reduce the tumour size, making the surgical defect significantly smaller than it would have occurred with initial untreated lesion.…”
Section: Discussionmentioning
confidence: 85%
“…Several small retrospective studies and case reports have documented successful treatment of both operable and inoperable periocular laBCC, with preservation of the eye in all patients. [59][60][61] An open-label trial of 15 patients with advanced BCC who received neoadjuvant vismodegib for 3 to 6 months prior to surgical excision reported a mean reduction of 35% in the final surgical defect size, with no recurrence at 22 months. 62,63 The latest and largest study performed was a phase 2 open-label trial known as VISMONEO, where 44 of 55 laBCC patients (80%) receiving neoadjuvant vismodegib for a mean duration of 6 months (range, 4-10 months) achieved the primary end point of tumor surgical downstaging.…”
Section: Neoadjuvant Administrationmentioning
confidence: 99%